Experimental Study on Work of Adsorption Gas Expansion After Coal and Gas Outburst Excitation - Zhao, Yi; Niu, XinGang (Frontiers in Earth Science, 2022)
Coal and gas outburst is an extremely complex dynamic phenomenon of mine gas, which is mainly manifested in a very short time. A large number of coal and rock are thrown out from the coal body to the mining space and accompanied by a large number of high pressure gas. In the process of coal and gas outburst, the internal energy consumption of gas is composed of two parts, one is used to throw out broken coal and rock mass, the other is used to pulverized broken coal. In this paper, from the perspective of energy dissipation, the experiment of broken coal ejection with different coal particle size, different adsorption gas and pressure is studied. The characteristics of coal ejection are studied and analyzed, and the proportion of adsorbed gas participating in outburst work is quantitatively analyzed. The results show that after outburst excitation, residual gas will continue to desorb and work on outburst until the power is insufficient to throw coal body ; compared with air, CO2 gas has a stronger ability to work on outburst, and the outburst coal is thrown far away, and the pulverization effect is stronger. Through the energy analysis in the process of outburst, the results show that when the particle size of coal sample is consistent, the greater the outburst pressure is, the larger the desorption amount of adsorbed gas is, and the larger the volume involved in outburst work is. When the test gas is consistent with the outburst pressure, the gas desorption amount of small size coal sample is more, the desorption gas has stronger ability to work on outburst, and the proportion of participating in outburst work is higher. The crushing degree of coal plays an important role in the expansion and release of gas internal energy.